The rationalization for bank branches: Italy vs. Poland - Włodarczyk, Bogdan; Burchi, Alberto (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
Banks have undergone an extensive expansion process in their distribution network. Today, Italy is considered an over-branched country. In Poland on the other hand, we have seen the development of a banking network in a period of economic transformation. All operators have been forced to begin a process of rationalization in their distribution networks. Poland vs. Italy may be a good example of a comparison of the changes taking place in the area of the optimization of the distribution networks of the mature banking market in Italy with the constantly growing banking market in Poland. The aim of this work was to observe on-going processes and to analyse it. On the one hand, there was a focus on the evolutionary point of view causing changes in the optimization network.On the other hand, attention was paid to the identification of the determinants affecting the percentage of persons holding a bank account in Poland, Italy, and in 27 countries of the European Union
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 482, s. 272-294
Keywords: bank branches; rationalization; market structure; banki; racjonalizacja; struktura rynkowa